Trends and strategies to enhance triacylglycerols and high-value compounds in microalgae - Lisa Schueler, Lisa M. Schueler (2019)
Microalgae are important sources of triacylglycerols (TAGs) and high-value compounds such as carotenoids and long-chain polyunsaturated fatty acids (LC-PUFAs). TAGs are feedstocks for biofuels or edible oils; carotenoids are used as pigments in the food and feed industries; and LC-PUFAs are beneficial for human health, being also key to the correct development of fish in aquaculture. Current trends in microalgal biotechnology propose the combined production of biofuels with high-value compounds to turn large-scale production of microalgal biomass into an economically feasible venture. As TAGs, carotenoids and LC-PUFAs are lipophilic biomolecules, they not only share biosynthetic precursors and storage sinks, but also their regulation often depends on common environmental stimuli. In general, stressful conditions favor carotenoid and TAGs biosynthesis, whereas the highest accumulation of LC-PUFAs is usually obtained under conditions promoting growth. However, there are known exceptions to these general rules, as a few species are able to accumulate LC-PUFAs under low light, low temperature or long-term stress conditions. Thus, future research on how microalgae sense, transduce and respond to environmental stress will be crucial to understand how the biosynthesis and storage of these lipophilic molecules are regulated. The use of high-throughput methods (e.g. fluorescent activated cell sorting) will provide an excellent opportunity to isolate triple-producers, i.e. microalgae able to accumulate high levels of LC-PUFAs, carotenoids and TAGs simultaneously. Comparative transcriptomics between wild type and tripleproducers could then be used to identify key gene products involved in the regulation of these biomolecules even in microalgal species not amenable to reverse genetics. This combined approach could be a major step towards a better understanding of the microalgal metabolism under different stress conditions. Moreover, the generation of triple-producers would be essential to raise the biomass value in a biorefinery setting and contribute to meet the world's rising demand for food, feed and energy.